Proceedings of the Twenty-Fifth Annual ACM-SIAM Symposium on Discrete Algorithms 2013
DOI: 10.1137/1.9781611973402.96
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Optimal Mechanism Design

Abstract: Myerson's seminal work provides a computationally efficient revenue-optimal auction for selling one item to multiple bidders [18]. Generalizing this work to selling multiple items at once has been a central question in economics and algorithmic game theory, but its complexity has remained poorly understood. We answer this question by showing that a revenue-optimal auction in multi-item settings cannot be found and implemented computationally efficiently, unless ZPP ⊇ P #P . This is true even for a single addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(98 citation statements)
references
References 23 publications
1
97
0
Order By: Relevance
“…They also show that in the single-buyer setting with identically distributed items, offering the grand bundle at some optimal price guarantees a O( 1 log n )-fraction of the optimal revenue. At the same time, exact polynomialtime solutions have been recently precluded by [8], where it is shown that computing optimal mechanisms is #P hard, even when there is a single additive bidder whose values for the items are independent of support 2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also show that in the single-buyer setting with identically distributed items, offering the grand bundle at some optimal price guarantees a O( 1 log n )-fraction of the optimal revenue. At the same time, exact polynomialtime solutions have been recently precluded by [8], where it is shown that computing optimal mechanisms is #P hard, even when there is a single additive bidder whose values for the items are independent of support 2.…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that, unlike the single-item case, the optimal mechanism need not be deterministic [17,13,14,11]. Here is an example from [8]: Suppose there are two items and an additive bidder whose values are independent and uniformly distributed in {1, 2} and {1, 3} respectively. In this scenario, the optimal mechanism offers the bundle of both the items at price 4; it also offers at price 2.5 a lottery that, with probability 1/2, gives both items and, with probability 1/2, offers just the first item.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it may involve bundling and lottery pricing, the menu size could be very large or even infinite [32,29,24,18]. The task of finding the optimal mechanism could be computationally intractable [17,19].…”
Section: Related Workmentioning
confidence: 99%
“…In some special cases the optimal mechanism is relatively simple, e.g., in a natural case of values for different goods being independent and uniform [0, 1], the optimal mechanism offers a menu with separate prices for each of the items and a price for the bundle (despite a simple answer the proof of this fact is quite nontrivial [29].) For general distributions it has been shown that randomization might be necessary and even that the seller might have to offer an infinite menu of lotteries [24,19]. On the other note, the revenue of the optimal auction may be non-monotone [25] when the buyer's values in the prior distribution are moved upwards (in the stochastic dominance sense).…”
Section: Introductionmentioning
confidence: 99%